2008
DOI: 10.1128/jvi.00194-08
|View full text |Cite
|
Sign up to set email alerts
|

The Envelope of Intracellular African Swine Fever Virus Is Composed of a Single Lipid Bilayer

Abstract: African swine fever virus (ASFV) is a member of a family of large nucleocytoplasmic DNA viruses that include poxviruses, iridoviruses, and phycodnaviruses. Previous ultrastructural studies of ASFV using chemical fixation and cryosectioning for electron microscopy (EM) have produced uncertainty over whether the inner viral envelope is composed of a single or double lipid bilayer. In this study we prepared ASFV-infected cells for EM using chemical fixation, cryosectioning, and high-pressure freezing. The appeara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
20
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…This model, however, has been recently questioned, and based on data obtained using samples prepared by high-pressure freezing, it has been suggested that the inner envelope of ASFV consists of a single lipid bilayer (28). The icosahedral capsid layer, formed by protein p72, is then progressively assembled on one side of this envelope, while on the other side, the core shell domain, mainly constituted by the processing products of the polyproteins pp220 and pp62, is simultaneously constructed (6,7,20,26).…”
mentioning
confidence: 99%
“…This model, however, has been recently questioned, and based on data obtained using samples prepared by high-pressure freezing, it has been suggested that the inner envelope of ASFV consists of a single lipid bilayer (28). The icosahedral capsid layer, formed by protein p72, is then progressively assembled on one side of this envelope, while on the other side, the core shell domain, mainly constituted by the processing products of the polyproteins pp220 and pp62, is simultaneously constructed (6,7,20,26).…”
mentioning
confidence: 99%
“…Phycodnaviruses, together with mimivirus, iridoviruses, asfarviruses, ascoviruses, and poxviruses have a common evolutionary ancestor and they are among the largest and most complex viruses known. Collectively these viruses are referred to as nucleocytoplasmic large DNA viruses (NCLDV) (3)(4)(5)(6)(7)(8). With the exception of the poxviruses and ascoviruses, all of these viruses are roughly icosahedral in shape and have surfaces consisting of hexagonally closed packed arrays of capsomers organized into tri-and pentasymmetrons (SI Text).…”
mentioning
confidence: 99%
“…The traditional view of the inner envelope as formed by two tightly opposed membranes derived from ER collapsed cisternae (7,59,60) has recently been challenged by the careful examination of the width of the internal membrane of viral particles and the single outer mitochondrial membrane, carried out using chemical fixation, cryosectioning, and high-pressure freezing (34). The results suggest that the inner envelope of ASFV is a single lipid bilayer, which raises the question of how such a structure can be generated and stabilized in the precursors of the ASFV internal envelope.…”
mentioning
confidence: 99%
“…Intracellular particles are formed by an inner viral core, which contains the central nucleoid surrounded by a thick protein coat, referred to as core shell. This core is enwrapped by an inner lipid envelope (7,34) on top of which the icosahedral capsid is assembled (26,27,31). Extracellular virions possess an additional membrane acquired during the budding from the plasma membrane (11).…”
mentioning
confidence: 99%